New English Teachers’ Perspectives on Anonymous Peer Feedback for Grammar Awareness - Fauziyah, Ni’fatul; Lestari, Lies Amin; Munir, Ahmad (Journal of English Language and Education, 2026)
This study examines novice English course teachers’ views on the use of anonymous peer feedback as a means of enhancing grammar awareness. The participants consisted of 14 newly appointed English teachers at a language course institution in Sidoarjo who took part in a grammar-awareness workshop within a Teacher Induction Program. Adopting a qualitative descriptive approach, the study gathered data through classroom observation and a post-workshop questionnaire. The results reveal that anonymous peer feedback fostered more active engagement, lowered participants’ anxiety, and supported reflective awareness of grammatical accuracy. In addition, the workshop enabled teachers to recognize recurring grammatical errors and encouraged self-regulated learning during professional development. These findings suggest that anonymous peer feedback can serve as an effective and supportive strategy for strengthening grammar awareness in English teacher induction and training contexts.